PENGARUH PEMBIAYAAN (BAGI HASIL dan JUAL BELI), FINANCING TO DEPOSIT RATIO (FDR), DAN NON PERFORMING FINANCING (NPF) TERHADAP PROFITABILITAS BANK NON DEVISA SYARIAH (Tahun penelitian 2015 -2017) - Budihariyanto Budihariyanto; Afifudin Afifudin; Junaidi Junaidi (Universitas Islam Malang, 2018)
ABSTRACTThe purpose of this research is to examine the effect of profit sharing financing,sale and purchase financing, FDR and NPF on the profitability level of Islamiccommercial banks. The sample in this study are 6 banks which are included asnon-foreign exchange sharia commercial banks. In this study the samplingtechnique used purposive sampling. The analysis technique used in the study ismultiple regression analysis. The results of this study indicate that the financingof profit sharing, sale and purchase financing and FDR has a positive influenceon profitability and the NPF has a negative effect on profitability.Keywords: sharing financing, purchase financing, FDR, NPF